Activation of O2 by Organosilicon Reagents Yields Quantitative Amounts of H2O2 or (Me3Si)2O2 for Efficient O‐Transfer Reactions. Issue 12 (27th November 2018) - Yamamoto, Keishi; Tanaka, Shinji; Hosoya, Hiromu; Tsurugi, Hayato; Mashima, Kazushi; Copéret, Christophe
Abstract: Molecular oxygen is kinetically inert and rarely used as a primary oxidant for low temperature selective oxygenation reactions. Here, we show that O2 is converted into H2 O2 in almost quantitative yields (98 %) at ambient temperature and atmospheric pressure in the presence of bis(trimethylsilyl)‐1, 4‐cyclohexadiene1 . Similarly, the reaction of O2 with dihydro‐bis(trimethylsilyl) viologen2 and pyrazine3 yields bis(trimethylsilyl) peroxide (BTSP) in excellent yields (up to 99 %) at low temperature. Both processes demonstrate that readily available organosilicon reagents enable chemistry typically observed with mono‐oxygenase co‐enzymes, such as FADH2 and FMNH2, in biological systems, or at higher pressure via the industrial anthraquinone process. This efficient synthesis of H2 O2 and BTSP directly from O2 is particularly attractive for the preparation of the corresponding O‐17 and O‐18 labeled reagents without the need of large excess amounts of O2 . These are showcased in O‐atom transfer reactions to various organic or inorganic substrates, in a two‐step one‐pot process, making the rapid and on‐demand synthesis of large libraries of O‐labeled compounds readily possible. Abstract :